Comparing (99m)Tc-PSMA to (99m)Tc-MDP in Prostate Cancer Staging of the Skeletal System - Kabunda, Joseph (Clin Nucl Med, 2021)
This prospective study was aimed at assessing the ability of (99m)Tc-PSMA scan to detect bone metastases in prostate cancer (PCa) against (99m)Tc-MDP scan as a standard and assess the correlation of these modalities in PCa staging of bone involvement. PATIENTS AND METHODS: Forty-one patients (41) with histologically confirmed PCa were scanned using both methods. Planar imaging was performed with additional regional SPECT/CT 3 to 4 hours posttracer injection. Scans were reported as positive, negative, or equivocal. In the case of positive scans, lesions were quantified by each of the 3 reporters separately. Planar and SPECT/CT images were reported together to obtain the final report on each scan. RESULTS: Our preliminary results showed no significant difference in the detection of bone metastases between the 2 scans. (99m)Tc-PSMA detected 52 of the 55 bone lesions detected on (99m)Tc-MDP. However, (99m)Tc-PSMA provided extra information by reporting lymph nodal metastases in 7 patients and residual disease in the prostate in 2 patients with biochemical progression after radical therapy. In 1 patient, the PSMA scan resulted in change in management with patient now on (177)Lu-PSMA radioligand therapy. Equivocal findings were reported in 4 patients on (99m)Tc-MDP and none on (99m)Tc-PSMA. CONCLUSIONS: (99m)Tc-PSMA was comparable to (99m)Tc-MDP in detection of bone metastases and demonstrated an additional benefit of providing information on visceral disease. (99m)Tc-PSMA may be a better alternative to (99m)Tc-MDP in staging, restaging, and assessment of patients with biochemical progression after radical therapy of PCa in a resource-limited setup like ours while also assisting to detect patients eligible for PSMA-labeled radioligand therapy.